Afterimage - Pietromarchi, Bartolomeo 1968-; Rabottini, Alessandro 1976- (Mousse Publishing, 2023)
The publication accompanies the exhibition Afterimage curated by Bartolomeo Pietromarchi and Alessandro Rabottini for MAXXI L'Aquila (July 2, 2022–February 19, 2023). It is a visual reflection on memory and metamorphosis. The title refers to the afterimage, a phenomenon in which a visual stimulus persists on the retina even after it has disappeared. The exhibition explores the concept of permanence and transitoriness, rooted in human nature, history, and images. The catalog encapsulates the shared objectives of the exhibition and showcases the artistic contributions of twenty-six international artists who participated in the project. Each artist is thoughtfully presented through a dedicated technical sheet, complemented by captivating photographic documentation. This compilation beckons readers to embark on an immersive journey within the museum's gallery spaces, fostering intuitive associations between the showcased artworks, the architectural surroundings, and the historical backdrop of L'Aquila. Guiding this exploration are the eloquent words of the two curators, providing valuable insights into the visual odyssey that awaits within Afterimage
Mostra: "Afterimage", L'Aquila, MAXXI L'Aquila, 02.06.2022 - 05.03.2022
Keywords: Geschichte 2000-2023; Kunst; Erinnerung -- Motiv; Ausstellungskatalog -- MAXXI L'Aquila Museo nazionale delle arti del XXI secolo -- 02.06.2022-05.03.2022 -- L'Aquila